Improvement of crop rotations aimed at increasing their efficiency and conserving soil fertility in conditions of biological intensification - L. M. Kozlova; E. N. Noskova; F. A. Popov (Аграрная наука Евро-Северо-Востока, 2019)
The long-term research conducted in 2002-2017 in a long stationary experiment on studying different types of field crop rotations under conditions of the Kirov region showed that on sod-podzolic soils the loss of humus could be lowered using agro technical methods. The most critical of them include the reduction of a portion of bare fallow, transition to sown and green-manure fallow, expanded use of perennial legume and grain-legume crops and intercrop sowings. In eight-field crop rotations when using such means of a biologization as plowing of the root-stubble residues, aboveground mass of green-manure crops in fallow fields and intercrop sowings, the supply of organic substance was within 17.24-83.03 t/ha. By mineral-ization of this substance 7.64-11.51 t of humus were produced. In a crop rotation with bare fallow there is a negative balance of humus of -0.06 t/ha. The positive balance is obtained when using sown, green-manure fallows, intercrop sowings (two-three fields), and introduction of up to 25% perennial legumes to the structure of crop rotations. The formation of 0.96-1.44 t/ha of humus in the arable layer provides positive balance of 0.20-0.72 t/ha. The increase of the part of grain crops up to 62.5-75.0% in the structure of crop rotations resulted in rise of their efficiency up to 4.74-4.79 thousand fodder units. It was 0.27-0.32 thousand fodder units higher than in the control crop rotation with bare fallow. Dependence of productivity of agricultural crops on humus content was insignificantly negative (r = -0.16). The efficiency of the studied crop rotations depended considerably on the amount of productive moisture in the soil in a phase of ear formation of grain crops (r = -0.78) and on biological activity of the soil (r = -0.80).